Penerapan Pasal 90 Kitab Undang-Undang Hukum Pidana dalam Perkara Pidana Penganiayaan (Studi Putusan Nomor: 26/PID.B/2020/PN.TTN) - Octavia, Priandini Nur; Suyatna (Indonesian Journal Publisher, 2023)
The crime of abuse is an act committed by someone in any form that causes pain or suffering, even resulting in injury to the victim. Like the criminal act of abuse committed by Herianto bin Safrijal against Mauliddin bin Taliwa Auri who was selling vegetables at the Fajar City Integrated Market Complex, which started with a conversation between the perpetrator and the victim which resulted in Herianto bin Safrijal getting angry and then beating the victim. This research aims to determine the application of Article 90 of the Criminal Code and the judge's considerations in qualifying serious injuries in criminal abuse case number: 26/Pid.B/2020/PN. Ttn. This research uses a legislative, case and concept approach method with a normative juridical research type. the judge's consideration in handing down a verdict against Herianto bin Safrijal (Defendant) on the primary charge as stated in Article 351 paragraph (2) of the Criminal Code, namely assault resulting in serious injuries, with serious injuries meaning that the victim witness is unable to carry out activities or search work (selling vegetables) continuously as stated in Article 90 of the Criminal Code is not appropriate. Because the judge in giving considerations in qualifying serious injuries was not careful. So, to create a fair decision, and avoid decisions that are not supported by supporting evidence, the judge should be more careful and precise in considering the matters contained in the trial facts.